Tipe Kepemimpinan Transformasional Pada PT. Permata Sinergi Madani - Rachmawati Windyaningrum; Witri Fujiyulianti (Universitas Informatika dan Bisnis Indonesia, 2020)
This type of leadership has many forms according to the character of the leadership and the way of coordination in achieving work goals. PT. Permata Sinergi Madani is a retail company that sells special materials for solar energy. It has a leadership type characterized by a transformational leadership type. The purpose of this study is to describe the type of leadership of PT. Permata Sinergi Madani in terms of Ideal Influence, Inspirational Motivation, Intellectual Stimulation and Individual Consideration. The research method used is descriptive qualitative methodology with data collection techniques using participant observation. To determine the validity of the data, this study used triangulation of sources. The results of the analysis show that the type of transformational leadership in the aspect of ideal influence is that the leader influences others to move or carry out his vision, with good coordination or cooperation between the leader and his subordinates. Aspects of insporational motivation, leaders motivate only by demanding employees to obtain high profits. Intellectual stimulation aspect, provides an overview to employees in increasing the profit from the products sold through briefing activities. Aspects of individual consideration, leaders consider the relationship with employees to provide suggestions or input for the achievement of company profits. Conclusion The type of transformational leadership is more depicting the activities of the leader which are oriented towards work results that have a greater influence on employee performance.